Gauging the clinical significance of P-glycoprotein-mediated herb-drug interactions: Comparative effects of St. John's wort, echinacea, clarithromycin, and rifampin on digoxin pharmacokinetics - Gurley, Bill J. (2008)
Concomitant administration of botanical supplements with drugs that are P-glycoprotein (P-gp) substrates may produce clinically significant herb-drug interactions. This study evaluated the effects of St. John's wort and Echinacea on the pharmacokinetics of digoxin, a recognized P-gp substrate. Eighteen healthy volunteers were randomly assigned to receive a standardized St. John's wort (300 mg three times daily) or Echinacea (267 mg three times daily) supplement for 14 days, followed by a 30-day washout period. Subjects were also randomized to receive rifampin (300 mg twice daily, 7 days) and clarithromycin (500 mg twice daily, 7 days) as positive controls for P-gp induction and inhibition, respectively. Digoxin (Lanoxin(®) 0.25 mg) was administered orally before and after each supplementation and control period. Serial digoxin plasma concentrations were obtained over 24 hours and analyzed by chemiluminescent immunoassay. Comparisons of AUC((0-3)), AUC((0-24)), T(1/2), and C(max), were used to assess the effects of St. John's wort, Echinacea, rifampin, and clarithromycin on digoxin disposition. St. John's wort and rifampin both produced significant reductions (p<0.05) in AUC((0-3)), AUC((0-24)), and C(max), while clarithromycin increased these parameters significantly (p<0.05). Echinacea supplementation did not affect digoxin pharmacokinetics. Clinically significant P-gp-mediated herb-drug interactions are more likely to occur with St. John's wort than with Echinacea.